Registration of 'CP 13‐1223' sugarcane for Florida organic soils. Issue 1 (14th October 2021) - Islam, Md S.; Sandhu, Hardev; Zhao, Duli; Sood, Sushma; Momotaz, Aliya; Davidson, R. Wayne; Baltazar, Miguel; Gordon, Vanessa S.; McCord, Per; Arbelo Coto, Orlando
Abstract: 'CP 13‐1223' (Reg. no. CV‐204, PI 698176) sugarcane (a complex hybrid of Saccharum spp.) was released to growers in June 2020 for producing on muck soils in Florida. It was developed through a decade‐long cooperative research program between the USDA‐ARS, the University of Florida Everglades Research and Education Center, and the Florida Sugar Cane League, Inc. This cultivar resulted from a poly‐cross made at the USDA‐ARS Canal Point (CP) Sugarcane Field Station. CP 13‐1223 was released because of its high commercial recoverable sucrose (CRS) and stalk weight, and demonstrated acceptable levels of cane and sucrose yields on muck soils. CP 13‐1223 has resistance to orange rust, leaf scald, Sugarcane mosaic virus strain E, ratoon stunt disease, and smut, and moderate resistance to brown rust. Based on results from 13 harvests across replicated yield trials at five locations, CP 13‐1223 performed 29.6 and 9.5% higher in CRS and stalk weight, respectively, than the check cultivar 'CP 96‐1252'. It did not differ significantly from CP 96‐1252 in either cane yield, sucrose yield, or economic profitability. CP 13‐1223 is considered to have moderate tolerance to freezing in field tests.